Does acute caffeine ingestion improve high-intensity interval exercise performance? A systematic review and meta-analysis - Peng, Y.; He, L.; Du, W.; Liu, B.; Wang, X.; Gong, Y. (Frontiers in Physiology, 2026)
Objective: This systematic review and meta-analysis evaluated the effects of caffeine (CAF) on high-intensity interval exercise (HIIE) performance and examined potential moderators.